Cu2ZnSnS4/CNT composites as Pt free counter electrodes for dye sensitized solar cells with improved efficiency. (2016) - Nemala, Siva Sankar; Mokurala, Krishnaiah; Bhargava, Parag; Mallick, Sudhanshu
Abstract: Cu2 ZnSnS4 (CZTS) nanoparticles can be used potentially as a counter electrode (CE) in dye sensitised solar cells (DSSCs) because of its excellent electro catalytic activity, low internal resistance, good carrier transport and low cost. In the present work, we report the synthesis of CZTS nanoparticles by a simple solid state reaction and utilized as a CE in DSSCs. The electro chemical activity of the prepared CEs was measured by the cyclic voltametry. The photoelectric conversion efficiency (PCE) of the prepared cells was measured by solar simulator under 1 sun illumination (100 mW/cm 2, AM 1.5). The DSSCs with CZTS nanoparticles based counter electrodes relatively low (PCE) of 4.5%. However, the PCE was clearly improved by adding carbon nanotubes (CNTs) to CZTS nanoparticles and a maximum PCE of 6.3% was achieved, which is compared to the value of 6.8% with the Platinum (Pt) based CE.